Basicity of the System of Exponents with a Linear Phase in Sobolev Weight Space - Togrul Muradov; Valid Salmanov (Journal of Mathematics)
In the present paper a criterion for basicity of exponential system with linear phase is obtained in Sobolev weight space Wp,ρ1  (-π,π).